Role of JNK isoforms in the development of neuropathic pain following sciatic nerve transection in the mouse - Manassero Giusi; Repetto Ivan E; Cobianchi Stefano; Valsecchi Valeria; Bonny Christophe; Rossi Ferdinando; Vercelli Alessandro (SAGE Publishing, 2012)
Abstract Background Current tools for analgesia are often only partially successful, thus investigations of new targets for pain therapy stimulate great interest. Consequent to peripheral nerve injury, c-Jun N-terminal kinase (JNK) activity in cells of the dorsal root ganglia (DRGs) and spinal cord is involved in triggering neuropathic pain. However, the relative contribution of distinct JNK isoforms is unclear. Using knockout mice for single isoforms, and blockade of JNK activity by a peptide inhibitor, we have used behavioral tests to analyze the contribution of JNK in the development of neuropathic pain after unilateral sciatic nerve transection. In addition, immunohistochemical labelling for the growth associated protein (GAP)-43 and Calcitonin Gene Related Peptide (CGRP) in DRGs was used to relate injury related compensatory growth to altered sensory function. Results Peripheral nerve injury produced pain-related behavior on the ipsilateral hindpaw, accompanied by an increase in the percentage of GAP43-immunoreactive (IR) neurons and a decrease in the percentage of CGRP-IR neurons in the lumbar DRGs. The JNK inhibitor, D-JNKI-1, successfully modulated the effects of the sciatic nerve transection. The onset of neuropathic pain was not prevented by the deletion of a single JNK isoform, leading us to conclude that all JNK isoforms collectively contribute to maintain neuropathy. Autotomy behavior, typically induced by sciatic nerve axotomy, was absent in both the JNK1 and JNK3 knockout mice. Conclusions JNK signaling plays an important role in regulating pain threshold: the inhibition of all of the JNK isoforms prevents the onset of neuropathic pain, while the deletion of a single splice JNK isoform mitigates established sensory abnormalities. JNK inactivation also has an effect on axonal sprouting following peripheral nerve injury.